1996
DOI: 10.2105/ajph.86.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Trends and differentials in adolescent and young adult mortality in the United States, 1950 through 1993.

Abstract: Using data from the National Vital Statistics System and the National Longitudinal Mortality Study, this study examined mortality trends and differentials from 1950 through 1993 among US adolescents and young adults according to sex, race/ethnicity, education, family income, marital status, and cause of dealth. No appreciable reduction in youth mortality has occurred, especially among men. Declines in youth mortality from accidents have been nearly ofset by increases in death rates from homicide, suicide, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 10 publications
4
37
0
7
Order By: Relevance
“…Several studies have also shown substantial income and education gradients in all-cause injury mortality for children and youth. [8][9][10] A similar but more accentuated trend for education also was found for young adults aged 20 to 24 years. 9 Finally, blue-collar workers have been shown to be at increased risk for fatal occupational injuries 11,12 and motor vehicle crashes.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Several studies have also shown substantial income and education gradients in all-cause injury mortality for children and youth. [8][9][10] A similar but more accentuated trend for education also was found for young adults aged 20 to 24 years. 9 Finally, blue-collar workers have been shown to be at increased risk for fatal occupational injuries 11,12 and motor vehicle crashes.…”
supporting
confidence: 64%
“…[8][9][10] A similar but more accentuated trend for education also was found for young adults aged 20 to 24 years. 9 Finally, blue-collar workers have been shown to be at increased risk for fatal occupational injuries 11,12 and motor vehicle crashes. 13 The relation between SES and nonfatal injuries is less clear.…”
supporting
confidence: 64%
“…Vários autores enfatizam que nos Estados Unidos a população adolescente, especialmente os do sexo masculino, comparada com as outras faixas etárias, é a única que não está melhorando seu padrão de saúde e que tampouco está apresentando redução em sua mortalidade 16,17 .…”
Section: Discussionunclassified
“…La reducción que se ve es aún menor en hombres que en mujeres (Cardona et al, 2008). Mientras que en los primeros años de vida casi no existe diferencia en la mortalidad entre varones y mujeres, a partir de los 15 años se visualiza una razón de tasas o sobremortalidad masculina que, dependiendo la región, el año y la causa, puede alcanzar cifras tan abrumadoras como 17 (Viner et al, 2011;Cardona et al, 2008;Singh & Yu, 1996;Hueveline & Slap, 2002;Souza, 2005;Caicedo et al, 2004;Serfaty et al, 2003;Spinelli et al, 2015). A lo largo de ciertos periodos en ciertas regiones y entre ciertos grupos étnicos, ha aumentado la mortalidad en varones jóvenes en vez de disminuir (Cardona et al, 2008;Sing & Yu, 1996).…”
Section: Estudios Mundiales Y Regionalesunclassified
“…Sin embargo, las causas de mortalidad en esta edad responden a numerosos factores sociales que también son importantes desencadenantes para la reflexión en una sociedad. Sobre todo, se ha señalado las causas externas o violentas como una causa de muerte de creciente importancia en las edades de 15-24 años -y en algunos lugares aún más joven-muy especialmente en varones, quienes muestran una sobremortalidad que, dependiendo la región, puede ser mucho más que el doble de la tasa en mujeres (Viner et al, 2011;Cardona et al, 2008;Singh & Yu, 1996;Hueveline & Slap, 2002;Souza, 2005;Caicedo et al, 2004;Serfaty et al, 2003;Spinelli et al, 2015).…”
unclassified